Monitoring of the Microbial Landscape of Children with Congenital Heart Disease - G. V. Filonenko; A. A. Salamanina; D. L. Kyryk (Ukrainian Journal of Cardiovascular Surgery, 2016)
A microbiological survey of 704 children admitted to the operative treatment in the Children’s Cardiac Center has been carried out. We studied colonization of the mucous membranes and umbilical wound by opportunistic microorganisms with of basic determinants resistance. This data formed the basis for introduction of microbiological monitoring in the cardiac surgical hospital for the realization carrying out of preventive and control measures.